Stress management and anxiety reduction through EMG biofeedback/relaxation training upon junior high students - Lang, Darrel (My University, 1980)
The purpose of this study was to determine the effectiveness of Electromyographic biofeedback/relaxation training on the stress management and anxiety levels of junior high students. The subjects (N = 18) in this study were male and female eighth grade students at La Crescent Junior-Senior High School, La Crescent, Minnesota. The Stress Management Inventory was developed by the researcher to determine stress management in eighth grade students. The inventory was validated by a group of six jurors and reliability was determined by Hoyt's Analysis of Variance. Anxiety levels were determined using the State-Trait Anxiety Inventory. This study called for a pretest-posttest experimental design. To determine significance of stress management and anxiety change, the Mann-Whitney U-test was utilized. Differences in muscle tension were tested for significance with a t-test. Statistical analysis of data revealed no significant differences between groups at the .05 level of significance, although there was some observable change in muscle tension, anxiety, and stress management in the expected direction.
Keywords: Anxiety; Stress (Physchology); Biofeedback training.